The Effect of Clavicular Tunnel Position on Reduction Loss in Patients with Acute Acromioclavicular Joint Dislocations Operated with a Single-Bundle Suspensory Loop Device - Senel, Ahmet; Eren, Murat; Batur, Omer Cihan; Kaya, Oguz; Sert, Selman; Key, Sefa (Wiley, 2024)
ObjectiveThe treatment of acromioclavicular joint (ACJ) dislocations offers numerous options, and ongoing debates persist regarding their comparative effectiveness. Among these options, the suspensory loop device (SLD) is one of the most favored treatment modalities. Despite the observed high reduction loss rate associated with SLD, the treatment yields favorable clinical outcomes. This study aimed to investigate the clinical outcomes of patients with acute type 3 and 5 ACJ dislocations who underwent open and arthroscopic procedures using a single-bundle SLD, and to evaluate the effect of clavicular tunnel position on reduction loss.MethodsThirty-seven eligible patients diagnosed with acute type 3 and type 5 ACJ dislocation who underwent open and arthroscopic surgery with a single-bundle SLD between January 2015 and March 2022 were evaluated retrospectively. Demographic data and radiological measurements including coracoclavicular (CC) interval, clavicle length (CL), and implant distance (ID) were recorded. The ID/CL ratio was calculated and a value between 0.17 and 0.24 was considered as acceptable implant position. Reduction loss and other complications were noted. Patients were divided into two groups: open (Group 1) and arthroscopic (Group 2). Constant Murray Score (CMS) and Visual Analog Scale (VAS) were used for clinical and functional outcomes. Non-parametric tests were used for statistical analysis of variables.ResultsThe study included six females (16.2%) and 31 males (83.8%) with a mean age of 40.2 +/- 14.7 years (range: 20-75). The mean follow-up period was 22.3 +/- 16.7 months (range: 6-72). The average time from trauma to surgery was 6.3 +/- 5.3 days (range: 1-18). At the last follow-up, the CMS was 89.3 +/- 8.8 and the VAS score was 2.1 +/- 0.9. The mean ID/CL ratio was 0.19 +/- 0.1 and 19 patients (51.4%) were between 0.17 and 0.24. Reduction loss was observed in nine patients (24.3%). There were no significant differences between Group 1 and Group 2 regarding operation time (p = 0.998), ID/CL ratio (p = 0.442), reduction loss (p = 0.458), CMS (p = 0.325), and VAS score (p = 0.699). Of the 28 patients without reduction loss, 16 had an ID/CL ratio between 0.17 and 0.24 (p = 0.43). Furthermore, within the 0.17-0.24 interval, CMS was higher with an average of 91.8 +/- 5.1 compared to the other intervals (p = 0.559).ConclusionThe clinical and functional outcomes of acute type 3 and type 5 ACJ dislocation operated open and arthroscopically with single-bundle SLD are similar and satisfactory. A clavicular tunnel position in the range of 0.17-0.24 (ID/CL ratio) is recommended to maintain postoperative reduction. In this study, the effect of the clavicular tunnel distance/clavicular length ratio on the reduction loss in AC joint dislocation operated with single bundle SLD was evaluated. Based on our results and previous anatomical studies, we think that position of the clavicular tunnel with a ratio between 0.17 and 0.24 will maintance the reduction. image
Keywords: Acromioclavicular Joint Dislocation; Clavicular Tunnel Position; Reduction Loss; Single Bundle; Suspensory Loop Device